Clinical and laboratory risk factors for pulmonary tuberculosis recurrence in three pooled Indian cohorts - Krishnan, Sonya; Gupte, Nikhil; Paradkar, Mandar; Gupte, Akshay; Naik, Mrunmayi; Raskar, Swapnil; Suryavanshi, Nishi; Pradhan, Neeta; Gaikwad, Sanjay; Karyakarte, Rajesh; Lokhande, Rahul; Hanna Luke, Elizabeth; et al. (Frontiers in Tuberculosis, 2024)
Some individuals with drug-susceptible pulmonary tuberculosis (PTB) experience tuberculosis recurrence. To evaluate the incidence of and risk factors for recurrence following completion of antituberculosis therapy, we pooled data from three prospective observational Indian PTB cohorts with 1164 individuals 14 years old included in our analysis. Ninety-five (8%) experienced recurrence with an 8.5 cases/100 person-years recurrence incidence rate (95% confidence interval 6.9-10.3) and a median time to recurrence of 6 months. On multivariable logistic regression, month 2 culture positivity (aHR 2.06; 95% CI 1.17-3.63), BMI <17 mg/kg 2 (aHR 1.7; 95% CI 1.1-2.8), and male sex (aHR 1.92; 95% CI 1.05-3.51) were independent recurrence risk factors. Understanding risk factors for TB recurrence could enable clinicians to identify patients at risk for recurrence during antituberculosis therapy and may be used to alter patient care strategies, such as more frequent monitoring post treatment for high-risk individuals.